2011
DOI: 10.1111/j.1747-4949.2010.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Risk Factors, and Warning Signs of Stroke: A Systematic Review from a Gender Perspective

Abstract: Stroke is one of the leading causes of death globally. Awareness of stroke risk factors and warning signs are important for stroke prevention and seeking care. The purpose of this systematic review was to review existing literature that assessed the knowledge of stroke risk factors and warning signs and allowed separate gender analysis. We conducted a systematic review of all published studies (to August 2008) examining knowledge of stroke risk factors and warning signs that included women and provided results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
122
5
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(148 citation statements)
references
References 36 publications
(101 reference statements)
8
122
5
13
Order By: Relevance
“…People at highest risk of stroke were those least educated about it and men had lower levels of knowledge than did women. 1,8 Those at highest risk (ie older people and males) and ethnic minorities might have a poorer stroke understanding than the general population, and one study showed that many were unaware of their own higher risk status. A link was also suggested between a lower level of education and worse understanding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…People at highest risk of stroke were those least educated about it and men had lower levels of knowledge than did women. 1,8 Those at highest risk (ie older people and males) and ethnic minorities might have a poorer stroke understanding than the general population, and one study showed that many were unaware of their own higher risk status. A link was also suggested between a lower level of education and worse understanding.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent international reviews suggested inadequate understanding of the common risk factors and warning signs of stroke. 7,8 Stroke knowledge varies in different countries, which highlights the need for culturally appropriate national stroke campaigns. 8,9 American, Australian and French studies found that knowledge ranged from poor to 'moderate at best' .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yaşlanan nüfusa bağlı olarak 2030 yılında dünyada önde gelen ölüm nedenlerinden birinin inme olacağı tahmin edilmektedir (6). Türkiye'de toplam ölümler içinde %15 sıklığı ile ikinci sırada yer almaktadır (2,7).…”
Section: Introductionunclassified
“…İnme risk faktörlerinin farkındalığı inmeyi önlemede, inme alarm belirtileri farkındalığı ise acil tedaviye erişimde (4), akut inmede potansiyel tedavi seçeneklerinin arttırılmasında (revaskülarizasyon tedaviler; trombolitik ve mekanik trombektomi) ve inme sonrası daha iyi sonuçlar sağlamasında çok önemlidir (6,20,21,22,23,24,25).…”
Section: Introductionunclassified